Karakteristik Beberapa Submodul dari Suatu Modul - Afdhaluzzikri, Muhammad; Ambar, Jinan (Semeton Mathematics Journal, 2024)
In the context of group cohomology, free modules are used to construct projective resolutions, while torsion modules play a significant role. In the theory of invariants, free modules describe all polynomial invariants, whereas torsion modules are relevant in the study of modular invariants. In elliptic curve cryptography, torsion points ensure security, with free modules used for arithmetic operations. The article also discusses the structure and properties of submodule types such as torsion, free, indecomposable, cyclic, and pure submodules, highlighting the importance of understanding the various applications of free and torsion modules.